Condições de trabalho e síndrome de burnout em atendentes de creche - Rosa, Elisângela de Britto (2023)
A significant number of children between zero and five years of age, due to their mothers' entry into the job market, require care from daycare attendants in the country. The work of these professionals, sometimes invisible to the eyes of society, involves a work routine with physical and mental overload, with negative effects on the worker himself and the children under his supervision. Care in the early stages of life is crucial for child development and interferes with the human aging process. Mental illness, through stress and Burnout syndrome, impacts the daily lives of education professionals in general and, consequently, daycare workers. The dissertation aims to analyze working conditions and the presence of Burnout syndrome in daycare attendants who work in Brazilian early childhood education. The cross-sectional, population-based study covers a sample of 110 participants from different states in Brazil. The research was disseminated through social networks and data collection was carried out through an online questionnaire, which brought together sociodemographic questions, health perception and the dimensions of exhaustion and disconnection from work included in the Oldenburg Burnout Inventory scale. (OLBI). The study, which is part of the research line on biopsychosocial aspects of human aging, presents the first scientific production, entitled "Exhaustion and disconnection from work in daycare attendants". The results suggest that being the head of a family implies higher levels of exhaustion and disengagement at work. A similar trend was identified in relation to those participants undergoing treatment for depression. Considering the impacts of working conditions and illness in this professional category, the dissertation reinforces the importance of advancing studies on the subject, its repercussions both in the context of child development and in the aging processes of the caregiver and the child object of care .